Oral S2-Ag85 DNA Vaccine Activated Intestinal Cell dsDNA and RNA Sensors to Promote the Presentation of Intestinal Antigen - Dang Sheng; Sui Xin; Wu Dongxing; Wen Shubo; Song Yang; Chen Zeliang; Zhai Jingbo (Journal of Immunology Research)
Objective. To explore the molecular mechanism by which oral S2-Ag85DNA vaccines present intestinal antigens. The oral S2-Ag85 vaccine has been shown to protect the human body and effectively improve the titration of the vaccine by acting on intestinal mucosa cells and enhancing their immunogenicity. Method. Mice were immunized with the recombinant S2-Ag85 vaccine, and antibody secretion was then detected in the intestinal tissue. The molecular mechanisms of in vitro detection sensor molecules RIG-1, Pol III, and related conductor transductor molecules DAI, STING, AIM2, IRF3, and IRF7 were determined by separating intestinal IEC, DC, and IELC cells. Results. The S2-Ag85A vaccine was effective in activating dsDNA and RNA transduction pathways in intestinal cells and improving intestinal antigen presentation in mice.